2009
DOI: 10.1161/circresaha.108.179770
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2–Derived Prostaglandin F Mediates Endothelium-Dependent Contractions in the Aortae of Hamsters With Increased Impact During Aging

Abstract: Abstract-Hypertension and vascular dysfunction result in the increased release of endothelium-derived contracting factors (EDCFs), whose identity is poorly defined. We tested the hypothesis that endothelial cyclooxygenase (COX)-2 can generate EDCFs and identified the possible EDCF candidate. Changes in isometric tension of aortae of young and aged hamsters were recorded on myograph. Real-time changes in intracellular calcium concentrations ([Ca 2ϩ ] i ) in native aortic endothelial cells were measured by ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
146
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 34 publications
17
146
3
4
Order By: Relevance
“…Meloxicam caused a decrease in NE constriction, which was greater in the Control old rats than young rats ( Figure 3D), suggesting that a COX-2 product is involved and related to age, according to the increase in COX-2 expression during aging ( Figure 1B). We have shown up-regulated in the presence of COX-1 and COX-2 in aortas from MS rats at six months of age, which is in accordance with previous results showing that both isoforms can contribute to endothelial dysfunction [22,53,59] . In several species, some authors have reported that PLA 2 and COX-2 are inflammatory proteins, and their expression is tightly regulated by various mediators [60][61][62] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 93%
See 2 more Smart Citations
“…Meloxicam caused a decrease in NE constriction, which was greater in the Control old rats than young rats ( Figure 3D), suggesting that a COX-2 product is involved and related to age, according to the increase in COX-2 expression during aging ( Figure 1B). We have shown up-regulated in the presence of COX-1 and COX-2 in aortas from MS rats at six months of age, which is in accordance with previous results showing that both isoforms can contribute to endothelial dysfunction [22,53,59] . In several species, some authors have reported that PLA 2 and COX-2 are inflammatory proteins, and their expression is tightly regulated by various mediators [60][61][62] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 93%
“…At least, in the rat aorta, EDCFs appear to be COX-1-derived prostanoids generated in the endothelium, which diffuse to contract the underlying vascular smooth muscle by activating thromboxane-prostanoid receptors [53] . Therefore, EDCF diffuses and subsequently stimulates thromboxane-prostanoid receptors in vascular smooth muscle [54] .…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells can release endothelium-derived contractile factors, which may include thromboxane A 2 , prostaglandin F 2α , leukotrienes and endothelin-1. Thromboxane A 2 and prostaglandin F 2α are released from the endothelium due to the activity of COX-2 [38,39]. The reduction of the contraction to UTP in the presence of DUP 697 indicated the involvement of thromboxane A 2 and prostaglandins in the contraction to UTP.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the contraction to UTP in the presence of DUP 697 indicated the involvement of thromboxane A 2 and prostaglandins in the contraction to UTP. These agents, after being released from the endothelium, may act on their receptors on VSMCs to cause contraction [39]. The different effects of DUP 697 on responses to UTP and ATP further suggest that they are acting on different receptors.…”
Section: Discussionmentioning
confidence: 99%